Changing trends in the incidence and spectrum of cancers between 1990 and 2021 among HIV-infected patients in Busan, Korea. Issue 6 (June 2023) - Lee, Soon Ok; Lee, Jeong Eun; Sim, Yong Ki; Lee, Shinwon; Ko, Woo Seog; Kim, Jinmi; Kang, Jin Suk; Son, Hyunjin; Lee, Sun Hee
Abstract: Background: Long-term follow-up data on cancer incidence and spectrum among human immunodeficiency virus (HIV)-infected individuals in Korea have been scarce. Material and Methods: This retrospective cohort study included HIV-infected individuals visiting a tertiary care hospital in Busan, South Korea between 1990 and 2021. The observation was divided into 4 periods. The incidence rate was calculated using direct standardization on age and sex, stratified by calendar period. Results: Of the 1, 297 patients, 92 patients (7.1%) were diagnosed with 97 cancers. Excluding 37 patients with prevalent cancer, 1, 260 patients were followed for a total of 8, 803.7 person-years (PYs), and 55 patients developed 60 incident cancers including 5 second primary incident cancers. In men, the AIDS-defining cancer (ADC) incidence decreased from 294.7 per 100, 000 PYs in 1990–1997 to 124.8 per 100, 000 PYs in 2014–2021, while the non-AIDS-defining cancer (NADC) incidence increased from 0 per 100, 000 PYs to 316.5 per 100, 000 PYs during the same period. The proportion of virus-unrelated NADCs (VU-NADCs) increased from 33.3% in 1998–2005 to 49% in 2014–2021. The proportion of human papillomavirus-associated cancers (HPVACs) has recently increased in both ADCs and NADCs. The median time from HIV diagnosis to their first cancer was 1.48 years for ADCs, 6.11 years for VR-NADCs, 8.3 years for VU-NADCs, and 11.5 years for HPVACs. Conclusion: The incidence of NADCs is increasing with the aging of HIV-infected patients, and thus, it is necessary to promote cancer screening and prevention programs.